2018
DOI: 10.1021/acs.inorgchem.8b01886
|View full text |Cite
|
Sign up to set email alerts
|

Manganese–Hydroxido Complexes Supported by a Urea/Phosphinic Amide Tripodal Ligand

Abstract: Hydrogen-bonds (H-bonds) within the secondary coordination sphere are often invoked as essential noncovalent interactions that lead to productive chemistry in metalloproteins. Incorporating these types of effects within synthetic systems has proven a challenge in molecular design that often requires the use of rigid organic scaffolds to support H-bond donors or acceptors. We describe the preparation and characterization of a new hybrid tripodal ligand ([H2pout]3–) that contains two mono-deprotonated urea group… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 57 publications
3
18
0
Order By: Relevance
“…This design principle was first incorporated in complexes of our tripodal ligands with sulfonamido groups ([RST] 3– , Figure D) that produced a variety of discrete heterobimetallic complexes with M III −(μ–OH)−LA II cores (M III = Mn, Fe, Co, Ga). In these systems, two SO groups and the hydroxido ligand form an auxiliary site that is capable of facially binding a second metal ion. However, our studies found that sulfonamido groups do not provide a strong enough ligand field to stabilize more highly oxidized complexes. ,, We reasoned that redesign of the ligand to [poat] 3– would provide access to an Fe IV –oxido species capable of supporting a LA II at its auxiliary binding site and allow us to evaluate changes in the structural and spectroscopic properties of the Fe IV –oxido species upon LA II binding.…”
Section: Results and Discussionmentioning
confidence: 95%
See 3 more Smart Citations
“…This design principle was first incorporated in complexes of our tripodal ligands with sulfonamido groups ([RST] 3– , Figure D) that produced a variety of discrete heterobimetallic complexes with M III −(μ–OH)−LA II cores (M III = Mn, Fe, Co, Ga). In these systems, two SO groups and the hydroxido ligand form an auxiliary site that is capable of facially binding a second metal ion. However, our studies found that sulfonamido groups do not provide a strong enough ligand field to stabilize more highly oxidized complexes. ,, We reasoned that redesign of the ligand to [poat] 3– would provide access to an Fe IV –oxido species capable of supporting a LA II at its auxiliary binding site and allow us to evaluate changes in the structural and spectroscopic properties of the Fe IV –oxido species upon LA II binding.…”
Section: Results and Discussionmentioning
confidence: 95%
“…To further evaluate the effects of these intramolecular H-bonding interactions on Fe IV –oxido species, we prepared the ligand [poat] 3– , which contains deprotonated phosphinic amide groups instead of ureas. The design of this ligand was inspired by the work of Stephen and the ability of the ligand to stabilize high-valent complexes relies on the fact that deprotonated phosphinic amides and ureas produce comparable ligand fields . However, the local environments that surround the Fe–oxido centers in complexes of [poat] 3– are different from those in complexes of [H 3 buea] 3– because the [poat] 3– ligand lacks the intramolecular H-bond donors contained in [H 3 buea] 3– .…”
Section: Results and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In a subsequent piece, Borovik and co-workers reported a ligand bearing two urea groups along with a phosphinic amide arm (Scheme 20, bottom right). 54 In this example, a {[Mn(III)]-OH} compound was accessed that bore three intramolecular H-bonding interactions where the phosphinic amide served as an acceptor and the urea arms served as donors. Such {[Mn(III)]-OH} compounds are rare, as they often react to form ill-defined multinuclear species.…”
Section: Tripodal Ligandsmentioning
confidence: 99%